1990
DOI: 10.1097/00001888-199005000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Results of a survey on the use of standardized patients to teach and evaluate clinical skills

Abstract: In 1989, a survey was sent to each U.S. and Canadian medical school requesting information about how standardized patients are used for teaching and evaluating clinical skills, and 95% of the schools responded. Although there was widespread use of standardized patients throughout the curricula, the role and training of these patients varied markedly within a given school as well as across schools. One outcome of this survey is the development of a network to share resources, protocols, and training material to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0
2

Year Published

1991
1991
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(66 citation statements)
references
References 0 publications
0
63
0
2
Order By: Relevance
“…Recent research using patient simulators has demonstrated the feasibility, utility, and validity of such clinical evaluations. [41][42][43][44][45][46][47] A second approach to the gold standard problem is evaluation of a single performance by a group of expert judges who all observe the same performance and then rate the performance independently (perhaps using videotape). A third, more common approach in traditional clinical performance assessment involves a comparison of the ratings of a group of expert judges who observed the same practitioner across an uncontrolled and undocumented range of situations and tasks in natural environments.…”
Section: Utilitymentioning
confidence: 99%
“…Recent research using patient simulators has demonstrated the feasibility, utility, and validity of such clinical evaluations. [41][42][43][44][45][46][47] A second approach to the gold standard problem is evaluation of a single performance by a group of expert judges who all observe the same performance and then rate the performance independently (perhaps using videotape). A third, more common approach in traditional clinical performance assessment involves a comparison of the ratings of a group of expert judges who observed the same practitioner across an uncontrolled and undocumented range of situations and tasks in natural environments.…”
Section: Utilitymentioning
confidence: 99%
“…SPs have been successfully used in medical education to teach students about medical interviews for taking a history or obtaining informed consent and in some cases basic physical examinations such as auscultation and palpation (13,14). Medical students can practice and improve their clinical skills by sessions with SPs and by feedback provided from teachers and SPs before encounter with real patients ( Figure 1F).…”
Section: Simulated or Standardized Patientsmentioning
confidence: 99%
“…Full-time faculty, instructors and administrative staff are essential for management of SBME in a clinical skills laboratory because a variety of works, such as program development, maintenance of equipment, recruitment and training of SPs, coordination of leaders and learners, booking services, setting preparation and clean up, are required for SBME (3,13,21).…”
Section: Faculty Instructors and Administrative Staffmentioning
confidence: 99%
“…Until now, the tendency has been for real patients to be used in the History Taking Station (Station 2) and trained surrogate patients 10 in the Communication Skills and Ethics Station (Station 4).…”
Section: 'Talking' Stations: History Taking (Station 2) and Communicamentioning
confidence: 99%